Imparting Nutrition Knowledge to School Children and Communities: The Role of Orange Fleshed Sweet Potato in Nutrition : The Role of Orange Fleshed Sweet Potato in Nutrition - Mbela, Domina Esther (European Journal of Applied Sciences, 2021)
Consumption of orange-fleshed sweet potato is essential in combating malnutrition. To date, researchers have made many efforts to introduce bio-fortified foods to increase nutrient adequacy. This study conducted baseline and end-line surveys to 480 students and 48 teachers in the three districts of Tanzania, namely Mkuranga, Bukoba, and Missenyi, and was trained on nutrition education. The knowledge on orange-fleshed sweet potato (OFSP) nutrition value increased from 0.40% to 74.21% for students and from 5.30% to 97.72% for teachers. Both students and teachers showed to score high dietary diversity. Teachers and farmers/women of reproductive age practiced boiling OFSP with peels which is the appropriate method for preventing nutrient loss. These results show that students and teachers gained knowledge of the nutrition benefits of OFSP. The study found that more than half (60.80%) of students and 25.00% of teachers in their households still cook potatoes after peeling; the practice that can lead to the loss of some nutrients, especially water-soluble vitamins. There was an increase in OFSP consumption by teachers (100%), students (99.2%), and farmers/women of reproductive age (76.3%). The majority of family members preferred sweet potato consumption at the end line survey by 62%. The study also showed an increase in student's school attendance from 85.06% (2015) to 91.56% (2018). This study suggests more effort is needed to increase the adoption and utilization of OFSP through a developed partnership with agro-processors for viable processed products.